Prevalence and resistance to antibiotics for Aeromonas species from retail fish in Malaysia - Radu, Son; Ahmad, Noorlis; Ling, Foo Hooi; Reezal, Abdul (Elsevier Science B.V., 2003)
A total of 87 market fish samples representing five types of fish were evaluated for the presence of Aeromonas spp. Of the samples examined, 69%, 55%, 11.5% and 2.3% harbored Aeromonas spp., A. veronii biovar sobria, A. hydrophila and A. caviae, respectively. The 60 isolated Aeromonas spp. strains were further examined for hemolytic activity, resistance to antimicrobial agents and presence of plasmids. Hemolytic activity varied widely among the isolated strains. Though all the isolates demonstrated resistance to three or more of the antibiotics tested, all were susceptible to ceptazidime. Thirty-four (56.7%) of the sixty isolates harbored plasmids, with sizes ranging from 2.3 to 15.7 kb. These results indicate that hemolytic, multiple antibiotic resistant and genetically diverse aeromonads are easily recovered from fish in this region.